Protection level of an intermediate vaccine against gumboro disease in laying hens - León R., Natalia (2012)
This study evaluated the protection conferred by a vaccine against Gumboro disease in laying hens. Three hundred Isa Brown one-day-old chicks were equally distributed in three groups. Groups A and B were vaccinated, twice, at 9 and 24 days old with an intermediate-intermediate strain (2512), and group C remained unvaccinated. Groups B and C were challenged at 32 days old with the F52/70 strain through the eye. Bursal index, bursa/spleen relationship and microscopic lesions of the bursa, spleen and thymus after vaccination were evaluated at 1, 35 and 45 days old. Antibody titers by an indirect ELISA study but not in birds of groups A and B. The bursal index values in the three groups were compatible with bursal atrophy. Histopathological lesions were severe in the three groups. At 45 days of age, birds of group C had the major seroconvertion (3997), while groups A and B presented similar antibodies titers. It is concluded that although the use of an intermediate vaccine at 9 and 24 days old caused bursal atrophy, the vaccine also gave sufficient protection against Gumboro disease.